Characterization of a cDNA clone encoding the calmodulin-binding domain of mouse brain calcineurin. - Kincaid, R L (1988)
A cDNA clone corresponding to a portion of the catalytic subunit of calmodulin (CaM)-dependent phosphoprotein phosphatase (calcineurin) was isolated from a murine brain library by expression vector immunoscreening. A beta-galactosidase fusion protein that reacted on Western blots with anti-calcineurin antibodies and biotinylated CaM was purified in preparative amounts using CaM-Sepharose affinity chromatography. Partial digestion of the hybrid protein with Staphylococcus aureus V-8 protease produced several immunoreactive peptides that appeared identical to fragments generated from authentic brain calcineurin. The 1111-base-pair (bp) EcoRI insert contained an open reading frame encoding a protein of 35 kDa followed by a 190-bp 3' noncoding region; seven peptides obtained by partial amino acid sequencing of the bovine brain enzyme were found in the deduced sequence. A domain approximately 12 kDa from the carboxyl terminus was deduced to be the CaM-binding site based on consensus structural features and a sequence of seven amino acids highly related to smooth muscle myosin light-chain kinase. Two regions with identity to protein phosphatases 1 and 2A were found in the amino half of the cloned sequence; however, the intervening sequence contained apparent insertions, suggesting splicing of subdomains. Thus, the structure of calcineurin is chimeric, consisting of conserved catalytic elements and a regulatory CaM-binding domain.